Relationship Between Pre-Pregnancy Body Mass Index (BMI), Number of Pregnancies, and Number of Nutrition Education Participation with Circumference Upper Arm (LILA) of Pregnant Women - Asep Afandi Aldisurya; Mayesti Akhriani; Desti Ambar Wati; Afiska Prima Dewi (CV Media Inti Teknologi, 2023)
Pregnant women's nutritional condition is determined by their Mid-Upper Arm Circumference (MUAC), which measures the body's state of balance. Factors influencing pregnant women's nutritional status include a history of body mass index before pregnancy, the number of pregnancies, and the number of participations in nutrition education. This study sought to discover the link between the history of body mass index before pregnancy, the number of pregnancies, and the number of participations in nutrition education with Mid- Upper Arm Circumference (MUAC) of pregnant women in the Working Area of the Tanjung Bintang Inpatient Public Health Center in 2022. The type of research is observational, analytic design, and cross-sectional, conducted from November to December 2022. The population in the study was 286, and the total sample was 80 respondents using the basic method of random sampling. The instrument used is a questionnaire. The data analysis used is the Spearman Correlation test. The results showed that the average Mid- Upper Arm Circumference (MUAC)of pregnant women was 25.54 with a standard deviation of 3.01, the average respondent's history of BMI was 22.272 kg/m2, the average number of respondents' pregnancies was 2.31 times, the average participation in nutrition education respondents as much as 2.93 times. The data analysis results showed a relationship between body mass index (p=0.0001) and the number of pregnancies (p=0.004) with the Mid- Upper Arm Circumference (MUAC)of pregnant women. There was no correlation between the number of participants in nutrition education (p=0.698) and the Mid- Upper Arm Circumference (MUAC)of pregnant women. It is hoped that the results of this study can add to knowledge about the relationship between the history of body mass index before pregnancy, the number of pregnancies, and the number of participants in nutrition education with MUAC for pregnant women.